Evaluating the Laser Output of the Micropulse P3 Laser Delivery Device Following Repeated Use. Issue 8 (August 2019) - Lun, Katherine; Suwandono, Maya E.; Koh, Victor; Chew, Paul T.
Abstract : Precis: Repeated use of the Micropulse P3 (MP3) probe during micropulse transscleral cyclophotocoagulation is associated with an increase in laser output over time. Purpose: The purpose of this study was to examine the laser efficacy of the MP3 probe following repeated use. Methods: This was an observational study carried out using Cyclo G6 Glaucoma Laser System with 6 MP3 laser delivery probes. Each probe was fired for 100 seconds, every 10 minutes until the probe was deactivated. The laser output was measured using a laser power meter. Maximum observed laser power output was also noted. Results: All probes were deactivated after 90 minutes (9 cycles) of use. Mean laser output of all 6 probes was determined, and results suggested an increase in output with time. When examining the differences in total laser output for each cycle, no significant differences were observed for the first 4 cycles, but not for the remaining 5 cycles, wherein the increased laser outputs were found to be significantly different from baseline (cycle 1). Conclusion: Findings suggest a possible increase in laser output with repeated use, especially after 4 cycles, and clinicians need to be cautious if they intend to use the probes repeatedly. Abstract : Supplemental Digital Content is available in the text.